(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Premessa. Specificità dell’ente ecclesiastico e diritto comune - 2. Lo scopo di religione o di culto. Finalità canoniche e finalità “pattuite”: antinomie e analogie - 3. Attività di interesse generale” di cui all’art. 5 d.lgs. n. 117 del 2017, missione caritativa e sociale della Chiesa e regolamentazione delle attività “diverse” da quelle di culto e religione - 4. Gli enti religiosi civilmente riconosciuti e la novella disciplina sugli enti del Terzo settore e dell’Impresa sociale: adempimenti canonici (regolamento, licenza scritta dell’ordinario e creazione di un patrimonio destinato) - 5. L’identificazione dei beni dell’ente canonico funzionali all’esercizio dell’attività di Terzo settore o di Impresa sociale: il bilancio separato. Conclusioni. Canonistic Reflections of the Reform of the Third Sector ABSTRACT: Third sector reform started with the delegation law n. 106 of 6 June 2016 undoubtedly involves canon law in its form and substance. The new legislation on the Third sector allows in a certain sense to "recover" many of the typically canonical activities of the religious entity within its "civil" structure in a way more coherent with the religious and canonical nature of the institution itself with respect to the law 222 of 1985. If we look at the activities that Legislative Decree 117 of 2017 calls (Article 5) "Activities of general interest", we highlight how many of them are specific and characterizing religious bodies of the Catholic tradition. The Author in particular highlights how the civilly recognized religious bodies, if they want to regulate some of their activities according to the new discipline on Third sector bodies and the Social enterprise, must undergo some canonical obligations (drafting of a regulation, written license of the Ordinary and creation of destined assets).